2012
DOI: 10.1080/14703297.2012.728379
|View full text |Cite
|
Sign up to set email alerts
|

Teaching undergraduate marketing students using ‘hot seating through puppetry’: an exploratory study

Abstract: Changes in preferred methods of learning among many students in recent years have challenged educators to introduce more interactive and experiential teaching methods. 'Hot seating'-where a person, such as an invited subject expert is interviewed by an audience, is a well-established interactive method of learning, but is often limited by availability of willing and suitable interviewees. In this exploratory study, university business undergraduates were required to interact with a lecturer-operated puppet rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…In nursing education, Tilbrook et al (2017) reported that puppets were used successfully in acute care paediatrics, while Reid-Searl et al (2017) described the use of puppetry for play therapy. Pearce and Hardiman (2012) illustrated that puppetry can also be used at the tertiary level by using the method of 'Hot Seating through Puppetry'. This method promoted engagement among business students; puppets were used to challenge students to explore and discuss contemporary marketing issues, including controversial products and ethics.…”
Section: Puppetry As a Teaching Methodologymentioning
confidence: 99%
“…In nursing education, Tilbrook et al (2017) reported that puppets were used successfully in acute care paediatrics, while Reid-Searl et al (2017) described the use of puppetry for play therapy. Pearce and Hardiman (2012) illustrated that puppetry can also be used at the tertiary level by using the method of 'Hot Seating through Puppetry'. This method promoted engagement among business students; puppets were used to challenge students to explore and discuss contemporary marketing issues, including controversial products and ethics.…”
Section: Puppetry As a Teaching Methodologymentioning
confidence: 99%
“…Puppetry art may be incorporated into the teaching of sciences to stimulate learners' positive attitudes and improve their performance since the puppets' characters are detached from the teacher's persona. They, therefore, add a unique teaching dimension that is flexible and controllable (Pearce & Hardiman, 2012). The use of puppetry art as an alternative teaching aid may improve teachers' and learners' self-efficacy, and make the teaching and learning of sciences more interesting (McGregor & Knoll, 2015) and meaningful.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Öte yandan yaratıcı drama, katılımcıların oluşturdukları bilgi ve deneyimlerin rolünü oynamayı içeren süreç eğilimli bir eğitim yöntemidir. İlgili literatür incelendiğinde, sosyal bilimler ve özellikle işletme alanında Öğrenciyi Merkeze Almak: Turist Rehberliği Eğitiminde Uzman Mantosu Yaklaşımı drama yöntemini kullanan hemen hemen tüm çalışmaların (Pearce, 2003;Pearce, 2006;Brennan ve Pearce, 2009;Pearce ve Hardiman, 2012) pazarlama eğitimi altında toplandığı görülmektedir. Eğitimde drama kullanımının yukarıda belirtilen yararlarına rağmen, turizm eğitimi literatüründe rol oynama tabanlı öğrenmeye (Armstrong, 2003) sınırlı bir ilgi olduğu anlaşılmaktadır.…”
Section: Tablo 1: Literatürde Yer Alan Yaratıcı Drama Kazanımlarıunclassified
“…Tablo 1'de, literatürde öne çıkan yaratıcı drama kazanımları sunulmaktadır. (Pearce, 2003;Pearce, 2006;Brennan ve Pearce, 2009;Pearce ve Hardiman, 2012) pazarlama eğitimi altında toplandığı görülmektedir. Eğitimde drama kullanımının yukarıda belirtilen yararlarına rağmen, turizm eğitimi literatüründe rol oynama tabanlı öğrenmeye (Armstrong, 2003) sınırlı bir ilgi olduğu anlaşılmaktadır.…”
Section: Li̇teratür İncelemesi̇ Yaratıcı Dramaunclassified